2015
DOI: 10.1016/j.ecolecon.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Quota compliance in TURFs: An experimental analysis on complementarities of formal and informal enforcement with changes in abundance

Abstract: The Environment for Development (EfD) initiative is an environmental economics program focused on international research collaboration, policy advice, and academic training. Financial support is provided by the Swedish International Development Cooperation Agency (Sida).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In terms of policy implications, this suggests that direct government action may still be necessary if widespread environmental improvements are to be achieved. However, governments should proceed cautiously as there is a growing body of experimental literature on common resource management (see Lopez et al 2012;Santis and Chávez 2015;Velez et al 2010;Vollan 2008;Cardenas and Stranlund 2000) that highlights the potential crowding-out effects of government intervention on intrinsic motivation to govern commons. Furthermore, the work of Dal Bó et al (2010) has shown that exogenously imposed governance regimes can be far less effective than those developed endogenously through democratic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of policy implications, this suggests that direct government action may still be necessary if widespread environmental improvements are to be achieved. However, governments should proceed cautiously as there is a growing body of experimental literature on common resource management (see Lopez et al 2012;Santis and Chávez 2015;Velez et al 2010;Vollan 2008;Cardenas and Stranlund 2000) that highlights the potential crowding-out effects of government intervention on intrinsic motivation to govern commons. Furthermore, the work of Dal Bó et al (2010) has shown that exogenously imposed governance regimes can be far less effective than those developed endogenously through democratic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Ito (2012) has also found similar results for community irrigation organizations in rural China. We also hope that our results add to the emerging field experimental literature on common pool resource management that primarily aims to investigate the crowding out effects of centralised interventions (see Vollan 2008;Velez et al 2010;Lopez et al 2012;Santis and Chávez 2015).…”
Section: Introductionmentioning
confidence: 91%
“…They empowered local stakeholders to undertake advocacy, education, and informal enforcement (Table 2). Informal enforcement, both alone and in combination with formal enforcement, can improve the effectiveness of protected areas (Santis and Chávez 2015). Empowerment at individual and collective scales is essential for the transformation that is necessary to achieve global sustainability (Andrijevic et al 2020;Messerli et al 2019).…”
Section: Policy and Management Implicationsmentioning
confidence: 99%
“…In recent years, there has been an increased effort to address this issue with controlled experiments that incorporate ecological characteristics, such as spatial resource dynamics (Janssen, 2010;Janssen et al, 2010), resource interdependencies (Lindahl et al, 2015), and endogenously-driven resource dynamics (Cárdenas et al, 2013). Osés-Eraso et al (2008) compare, for example, behavior under exogenous and endogenously-driven (human-induced) resource scarcity; Moreno-Sánchez and Maldonado (2010) and Blanco et al (2015) compare behavior under contrasting resource states (abundant versus scarce); Santis and Chaves (2015) investigate the role of quotas under contrasting resource states (abundant versus scarce); Kimbrough and Vostroknutov (2015) determine the effects of differing resource replenishment rates; and Hine and Gifford (1996) examine the effect of an uncertain resource growth rate, to name a few. We contribute to this strand of literature by introducing a request game 2 where the resource follows a logistic-type of resource dynamics, but where there is a latent regime shift -an endogenously-driven abrupt drop in the regrowth of the resource.…”
Section: Introductionmentioning
confidence: 99%